Hydrogeological effects of dredging navigable canals through lagoon shallows. A case study in Venice - Teatini, Pietro (2017)
For the first time a comprehensive investigation has been carried out to quantify the possible effects of dredging a navigable canal on the hydrogeological system underlying a coastal lagoon. The study is focused on the Venice Lagoon, Italy, where the port authority is planning to open a new 10m deep and 3km long canal to connect the city passenger terminal to the central lagoon inlet, thus avoiding the passage of large cruise ships through the historic center of Venice. A modeling study has been developed to evaluate the short (minutes), medium (months), and long (decades) term processes of water and pollutant exchange between the shallow aquifer system and the lagoon, possibly enhanced by the canal excavation, and ship wakes. An in-depth characterization of the lagoon subsurface along the channel has supported the numerical modeling. Piezometer and sea level records, geophysical acquisitions, laboratory analyses of groundwater and sediment samples (chemical analyses and ecotoxicity testing), and the outcome of 3-D hydrodynamic and computational fluid dynamic (CFD) models have been used to set up and calibrate the subsurface multi-model approach. The numerical outcomes allow us to quantify the groundwater volume and estimate the mass of anthropogenic contaminants (As, Cd, Cu, Cr, Hg, Pb, Se) likely leaked from the nearby industrial area over the past decades, and released into the lagoon from the canal bed by the action of depression waves generated by ships. Moreover, the model outcomes help to understand the effect of the hydrogeological layering on the propagation of the tidal fluctuation and salt concentration into the shallow brackish aquifers underlying the lagoon bottom.